In vitro propagation of Vanilla tahitensis Moore - R Lakshmanan, K J Madhusoodanan, K Mary Mathew, Y S Rao, Gilu Lizy George (Journal of Spices and Aromatic Crops, 2000)
A commercially viable protocol for mass propagation of Vanilla tahitensis, a cultivated species of vanilla, was standardized. A multiplication ratio of 1 : 4.7 was observed over a culture period of 60-70 days on benzylaminopurine (1 mgl-1) and a-naphthaleneacetic acid (O.1 mgl-1).